Model for predicting shrinkage of concrete using calcium sulfoaluminate cement blended with OPC, PFA and GGBS. (November 2020) - Yeung, Jaime SK.; Yam, Michael CH.; Wong, Y.L.
Abstract: Shrinkage is an important concern in concrete since it induces deformation and tensile stress, which may finally lead to cracking, in structural concrete members. Prediction for shrinkage of concrete is therefore an essential step at the structural design stage for determining required preventive measures. Following this need, various models are developed for predicting shrinkage of concrete in design codes. Unfortunately, their common shortcoming is the limited applicability to common cement types only. Lately in concrete repair applications, Calcium Sulfoaluminate Cement (CSAC) is becoming more and more popularly used due to its well-known properties of rapid strength gain and relatively low shrinkage. Nonetheless, since little study has been done for its long term shrinkage performance beyond the age of 28 days or even 56 days, the previously developed shrinkage prediction models are not applicable for concrete incorporating CSAC, not to mention when it is blended with other binder materials such as Ordinary Portland Cement (OPC), Pulversized Fuel Ash (PFA) and Ground Granulated Blastfurnace Slag (GGBS). In this study, shrinkage measurements were conducted for a total of 20 concrete mixes with different binder combinations but the same total binder content of 420 kg/cum of concrete and the same water to binder ratio of 0.45 for observing their shrinkage development trends at different ages up to 1 year. The GL2000 Model for shrinkage prediction given in ACI 209.2R-08 is adopted for comparing with the measured results. Different k factors to be put in the GL2000 Model for different binder materials are derived and verified with the shrinkage results. Highlights: We tested a total number of 20 concrete mixes with different binder combinations. Shrinkage values of each concrete mix up to the age of 365 days were measured. Influences of each binder material on concrete shrinkage development are discussed. The GL2000 Model for predicting long-term shrinkage is referred. K factors for different binders to be put in the GL2000 Model are derived.